Effects of experience and relative quality in tennis match performance during four Grand Slams - Cui, Y.; Gómez, M.-A.; Gonçalves, B.; Liu, H.; Sampaio, J. (International Journal of Performance Analysis in Sport, 2017)
The aim of this study was to explore the differences in technical, tactical and movement performance of professional male tennis players in Grand Slams, according to player's experience and relative quality. Match data of 1188 players competing in 2015-2017 Grand Slam tournaments were collected. Experience and relative quality (RQ) were used to classify players via cluster analysis, based on Cubic Clustering Criterion. Afterwards, a descriptive discriminant analysis was performed to identify the most important variables that best predict player clusters in each Grand Slam, and two discriminant functions were generated (p < 0.01). High-experienced Higher RQ Players (n = 337) outperformed other players in serve and return (fewer double faults, more second serve and return points won), rally winners and breaking opportunities while covering longer distance. Experienced Higher RQ Players (n = 267) hit faster serves and more aces, played more aggressively when returning (more return winners and unforced errors) and traversed less distance. Players approached the net with similar times in all Slams, showing that the current trend in male tennis is being tactically aggressive on all court surfaces. The effects of experience and RQ provide insights on individualized training and performance optimization in practice and competition.